Thermal efficiency and emission characteristics of a diesel-hydrogen dual fuel CI engine at various loads condition - Putrasari, Yanuandri; Praptijanto, Achmad; Nur, Arifin; Santoso, Widodo Budi; Pratama, Mulia; Dimyani, Ahmad; Suherman, Suherman; Wahono, Bambang; Wardana, Muhammad Khristamto Aditya; Lim, Ocktaeck (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2018)
Efforts to find alternative fuels and reduce emissions of CI engines have been conducted, one of which is the use of diesel hydrogen dual fuel. One of the goals of using hydrogen in dual-fuel combustion systems is to reduce particulate emissions and increase engine power. This study investigates the thermal efficiency and emission characteristics of a diesel-hydrogen dual fuel CI engine at various loads condition. The hydrogen was used as a secondary fuel in a single cylinder 667 cm3 diesel engine. The hydrogen was supplied to intake manifold by fumigation method, and diesel was injected directly into the combustion chamber. The results show that the performance test yielding an increase around 10% in the value of thermal efficiency of diesel engines with the addition of hydrogen either at 2000 or 2500 rpm. Meanwhile, emission analyses show that the addition of hydrogen at 2000 and 2500 rpm lead to the decrease of NOx value up to 43%. Furthermore, the smokeless emissions around 0% per kWh were occurred by hydrogen addition at 2000 and 2500 rpm of engine speeds with load operation under 20 Nm.